Quasicqnformal mappings with restrictions in measure - Ryazanov, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The principal result of the paper is a criterion of compactness for mappings quasiconformal in the mean. The semicontinuity of a deformation of homeomorphisms from the Sobolev class is also proved.